2013
DOI: 10.1186/1472-6963-13-262
|View full text |Cite
|
Sign up to set email alerts
|

Reforming healthcare systems on a locally integrated basis: is there a potential for increasing collaborations in primary healthcare?

Abstract: BackgroundOver the past decade, in the province of Quebec, Canada, the government has initiated two consecutive reforms. These have created a new type of primary healthcare – family medicine groups (FMGs) – and have established 95 geographically defined local health networks (LHNs) across the province. A key goal of these reforms was to improve collaboration among healthcare organizations. The objective of the paper is to analyze the impact of these reforms on the development of collaborations among primary he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 29 publications
(42 reference statements)
0
33
0
2
Order By: Relevance
“…We identified and included 43 systematic reviews 8, and 49 higher-quality studies from outside the UK using comparator group designs. In addition, 20 lower-quality non-UK studies (no comparator group) [243][244][245][246][247][248][249][250][251][252][253][254][255][256][257][258][259][260][261][262] and 37 qualitative studies from outside the UK were included within a 'light touch' analysis. Figure 2 provides a summary of the country of origin for the different types of study design.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…We identified and included 43 systematic reviews 8, and 49 higher-quality studies from outside the UK using comparator group designs. In addition, 20 lower-quality non-UK studies (no comparator group) [243][244][245][246][247][248][249][250][251][252][253][254][255][256][257][258][259][260][261][262] and 37 qualitative studies from outside the UK were included within a 'light touch' analysis. Figure 2 provides a summary of the country of origin for the different types of study design.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…A non-comparator study from Germany 219 reported that, although integration had enhanced staff relationships within the same service, relationships with organisations that were external to the initiative were less satisfactory. This was echoed by a non-comparator study from Canada, 246 which described reform as having a 'territorialising effect'. Collaboration with other organisations in the areas that were external to the network areas decreased (from 15% to 4% for collaboration with other primary care organisations and from 21% to 15% for collaboration with hospitals outside the network).…”
Section: Relationships Between Organisationsmentioning
confidence: 99%
“…The administrative merger of public organisations was the main mechanism the government of Québec chose to promote integration of health and social services [343536]. These Health and Social Services Centres were mandated by government to create Local Health Networks through formal and informal inter-organisational agreements [3738]. Various Local Health Networks addressing the needs of different sub groups of the population living on their territories were developed such as the Local Health Networks for Older People [39].…”
Section: Context Of the Studymentioning
confidence: 99%
“…Population-based planning is based on the identification of determinants of health to promote equitable access to services and health outcomes (World Health Organization 2008). The literature points to varying methods, policies and processes, across countries and regions, to base health planning on population approaches, and highlights tensions and challenges in embedding such a transformation in systems (Dubbs et al 2004;Carter et al 2007;Levesque et al 2011;Breton et al 2013).…”
Section: Introductionmentioning
confidence: 99%